ANALISIS HUKUM ISLAM TERKAIT AKAD TABARRU’ PADA TRADISI MARPEGE-PEGE DI DESA TORBANUA RAJA MANDAILING NATAL - Sumper Mulia Harahap; Raja Ritonga; Siti Rohimah (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
The marpege-pege tradition is one of the customs carried out by the people of Torbanua Raja Village in Mandailing Natal Regency. This activity provides financial assistance to people who will carry out the marriage. However, these activities are identical to accounts payable. This means that the person being helped must return the money given to him by another person at another time. This research will describe and analyze the tabarru contract in the marpege-pege tradition carried out by the people of Torbanua Raja village in Mandailing Natal Regency. This type of research is a qualitative type with the form of field studies. In collecting data, researchers conducted observations and interviews. Furthermore, the findings of the data were analyzed descriptively analytic. In conclusion, the tabarru' contract in the marpege-pege tradition carried out by the people of Torbanua Raja village in Mandailing Natal Regency is not completely ideal for a tabarru' contract. This is because in practice, the community still expects a return of money that has been given to other people when they marpege-pege.